O irmão que virou irmão: rupturas e permanências na conversão de membros do PCC ao pentecostalismo na Vila Leste - SP - Marques, Vagner Aparecido (2013)
The present dissertation investigates the conversion process of current and former PCC members to the Pentecostalism, in the Eastern area of São Paulo City. Our approach is to analyze a case study, through the journey of Kadu , brother in the church and also brother in the PCC party. The conversion trajectory of Kadu to the Pentecostalism will be seen through a new religious conversion paradigm. In that approach, the conversion is the result of a slow, gradual and not-immediate process, accompanied by numbers of crisis, as shown by a great deal of the religious conversion writings. Kadu´s conversion was not followed by the rupture/asceticism binomial; on the opposite, we could verify continuities along the former network, the PCC. This dual brotherhood is the main focus point of the research. Kadu also open some doors for the analyses of engaging networks existing in the Vila Leste neighborhood and its moral entrepreneurs. In the region of Vila Leste, Pentecostalism and PCC are entangled, and this reality will be analyzed in this work